Textiles and Clothing Sustainability Nanotextiles and Sustainability - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book highlights the sustainability aspects of textiles and clothing sector in light of nanomaterials and technologies. The invasion of nano in every industrial sector has been important and has made remarkable changes as well as posed new challenges, including the textiles and clothing sector. There is quite a great deal of research happening in terms of nano materials for textiles across the globe, some of which are covered in this book. .
1.Innovative approaches in nano textile finishes - Some insights on current trends Recent advances in nano textile finishes - An approach towards sustainability -- 2.Nano Chemicals and Effluent Treatment in Textile Industries -- 3.Insights into the functional finishing of textile materials using nanotechnology.
Keywords: Manufactures; Sustainability; Nanochemistry; Microtechnology; Microelectromechanical systems; Materials -- Analysis; Environmental management; Machines, Tools, Processes; Sustainability; Nanochemistry; Microsystems and MEMS; Characterization and Analytical Technique; Environmental Management